Model Konseptual Pengaruh Keberlanjutan terhadap Kinerja Industri Kecil dan Menengah - Hary Fandeli; Alizar Hasan; Elita Amrina (Universitas Andalas, 2020)
ABSTRACTSmall and Medium Enterprises (SMEs) are an industrial sector that greatly contribute to economic development in Indonesia. SMEs contributes positively to the increase in Gross Domestic Product (GDP) and absorption of productive labor. Therefore, SMEs are required to be able to achieve continuous performance improvement. Improving the performance of SMEs is also expected to be able to contribute to sustainable development. Sustainability then becomes a very important issue for the performance of SMEs. The performance evaluation of SMEs needs to be improved by considering the sustainability aspects. This study aims to design a conceptual model of the effect of sustainability to the performance of SMEs in West Sumatra. Indicators of sustainability and performance of SMEs were identified from literature study. Then, conducted the determination of indicators that are relevant to SMEs in West Sumatra and then sort the indicators based on terminology similarities. The results of the identification stage are 34 indicators of sustainability which are divided into three aspects and nine factors. Sustainability indicators consist of 16 indicators of social aspect, 11 indicators of environmental aspect, and 7 indicators of economic aspect. The next step is the validation of sustainability indicators by experts from practitioners, academics, and government. The validation results stated that all indicators are important and relevant to SMEs in West Sumatra. Then the conceptual model of the effect of sustainability to performance of SMEs is developed. This conceptual model is expected to be able to help SMEs in improving performance and competitiveness.Keywords: indicators, small and medium industry, sustainability, performance appraisal ABSTRAK Usaha Kecil dan Menengah (UKM) adalah sektor industri yang sangat berkontribusi terhadap pembangunan ekonomi di Indonesia. UKM berkontribusi positif terhadap peningkatan Produk Domestik Bruto (PDB) dan penyerapan tenaga kerja produktif. Oleh karena itu, UKM dituntut untuk dapat mencapai peningkatan kinerja yang berkelanjutan. Peningkatan kinerja UKM juga diharapkan dapat berkontribusi pada pembangunan berkelanjutan. Keberlanjutan kemudian menjadi masalah yang sangat penting bagi kinerja UKM. Evaluasi kinerja UKM perlu ditingkatkan dengan mempertimbangkan aspek keberlanjutan. Penelitian ini bertujuan untuk merancang model konseptual pengaruh keberlanjutan terhadap kinerja UKM di Sumatera Barat. Indikator keberlanjutan dan kinerja UKM diidentifikasi dari studi literatur. Kemudian, dilakukan penentuan indikator yang relevan dengan UKM di Sumatera Barat dan kemudian mengurutkan indikator berdasarkan kesamaan terminologi. Hasil tahap identifikasi adalah 34 indikator keberlanjutan yang dibagi menjadi tiga aspek dan sembilan faktor. Indikator keberlanjutan terdiri dari 16 indikator aspek sosial, 11 indikator aspek lingkungan, dan 7 indikator aspek ekonomi. Langkah selanjutnya adalah validasi indikator keberlanjutan oleh para ahli dari praktisi, akademisi, dan pemerintah. Hasil validasi menyatakan bahwa semua indikator penting dan relevan bagi UKM di Sumatera Barat. Kemudian model konseptual efek keberlanjutan terhadap kinerja UKM dikembangkan. Model konseptual ini diharapkan dapat membantu UKM dalam meningkatkan kinerja dan daya saing.Kata Kunci: indikator, industri kecil dan menengah, keberlanjutan, penilaian kinerja